2018
DOI: 10.1021/acs.jpclett.8b03595
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Emission Spectroscopy at X-ray Free Electron Lasers: Limits to Observation of the Classical Spectroscopic Response for Electronic Structure Analysis

Abstract: X-ray free electron lasers (XFELs) provide ultrashort intense X-ray pulses suitable to probe electron dynamics, but can also induce a multitude of nonlinear excitation processes. These affect spectroscopic measurements and interpretation, particularly for upcoming brighter XFELs.Here we elaborate on the limits to observing classical spectroscopy, where only one photon is absorbed per atom for a Mn 2+ in a light element (O, C, H) environment. X-ray emission spectroscopy (XES) with different incident photon ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In terms of quantifying the electronic structure effects of our measurements, when applying the rate equation model from Ref. 52 and adopting a 1s photoelectric cross section of ∼1.5 × 10 −20 cm 2 , we obtain an α value of 0.18 for R1. This parameter is formulated to encapsulate most of the pulse effects and allow for easy comparison between experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of quantifying the electronic structure effects of our measurements, when applying the rate equation model from Ref. 52 and adopting a 1s photoelectric cross section of ∼1.5 × 10 −20 cm 2 , we obtain an α value of 0.18 for R1. This parameter is formulated to encapsulate most of the pulse effects and allow for easy comparison between experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We thus assume in the present context that multiple ionization processes are sufficiently weak such that they do not influence our conclusions. While this may hold for XES measurements at synchrotron radiation sources, in the case of experiments at X-ray free electron lasers multiple ionized states might contribute considerably . Finally, the chemical sensitivity in K-emission may also arise from screening effects where the core hole potential is screened less efficiently for higher oxidation states.…”
Section: Introductionmentioning
confidence: 99%
“…While this may hold for XES measurements at synchrotron radiation sources, in the case of experiments at X-ray free electron lasers multiple ionized states might contribute considerably. 47 Finally, the chemical sensitivity in K-emission may also arise from screening effects where the core hole potential is screened less efficiently for higher oxidation states. This change in core hole screening affects 1s and 2p/3p electrons differently, resulting in an energy shift of the K-fluorescence lines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was demonstrated for serial femtosecond crystallography at Å resolution, that an X-ray probe pulse length on the order of tens of femtoseconds can ‘outrun’ the anticipated sample damage caused by an intense X-ray pulse containing 10 11 –10 12 photons focused down to a few μm 13 , 24 . Recent diffraction and spectroscopy data using micron-sized focused XFEL beams with intensity levels reaching 10 17 –10 18 W cm -2 have indicated that such intensities could trigger various damage mechanisms impacting experimental observables within the typical X-ray pulse durations of 10–30 fs 14 17 . In particular some efforts have been made to model and predict spectral shifts and tolerable photon densities for solution phase experiments 17 , and to describe the effect of solvent photoionization on the spectral shape 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent diffraction and spectroscopy data using micron-sized focused XFEL beams with intensity levels reaching 10 17 –10 18 W cm -2 have indicated that such intensities could trigger various damage mechanisms impacting experimental observables within the typical X-ray pulse durations of 10–30 fs 14 17 . In particular some efforts have been made to model and predict spectral shifts and tolerable photon densities for solution phase experiments 17 , and to describe the effect of solvent photoionization on the spectral shape 16 . In this letter we report a systematic time-dependent study of the effects of high XFEL pulse intensity on the electronic structure of Fe compounds at various metal concentration probed by X-ray emission spectroscopy (XES).…”
Section: Introductionmentioning
confidence: 99%